Implications Of Ingesting Soft Drink And Energy Drink On Hepatic Microcirculation Of Albino Rat - Saira Munawar; Faiza Irshad; G.P. William; Muhammad Suhail; Ayesha Yousaf; Ahmad Haris Suhail (Journal of Rawalpindi Medical College)
Objective: To compare the diameter of the centrilobular vein as well as its congestion along with that of sinusoids and portal vein of the rat liver after ingestion of caffeinated soft drinks and energy drinks which were given caffeinated soft drinks and energy drinks.